Analysis of Losses in Geostationary Intersatellite Optical Wireless Communication Links - Kamrun Nahar; Bobby Barua (International Journal of Satellite Remote Sensing, 2024)
The effective method to create a link between satellites is inter-satellite communication. Data is transmitted from one side to the other via a laser in this groundbreaking method. Optical networks, which offer continuous data transport over vast distances, are networks with high bandwidth efficiency. Inter-satellite optical wireless communication (Is-OWC) is a common method to transfer high-speed data between various satellites in free space. Is-OWC networks have undoubtedly innovated satellite communications networks recently. We have assessed the Is-OWC communication link's capability for high-speed data transfer in this work. In addition, we analyze some of the major obstacles that this technology faces and explain them. This study contrasts how various losses affect a geostationary satellite's receiving antenna's output power. The antenna elevation angle of an earth station needs to be determined in order to connect with satellites. Even if there are a lot of restrictions on satellite communication between the earth station and the satellite in both the uplink and downlink directions, air attenuations, rain, and noise. Therefore, some of the performance-limiting parameters, such as attenuation loss, elevation angle, pointing loss, free space path loss, divergence angle, antenna gain and Q-Factor, are identified in this work along with an attempt to examine how we might improve functionality
Keywords: Attenuation; Is-OWC; antenna gain; divergence angle; elevation angle; free space path loss; inter-satellite links (ISL); pointing loss; q-factor